Considering European Iron Age oppida and Comparative Urbanism: The Case of Bibracte and Manching - Moore, Tom; Hoppadietz, Ralf; Wendling, Holger; Winger, Katja (Journal of Urban Archaeology, 2023)
Abstract The Late Iron Age (second century bc to first century ad) agglomerations in Europe known as oppida have long defied easy categorization leading them to be described using various terms, such as proto-urban, rurban, and polyfocal. Despite the diversity of oppida many share characteristics, including large open spaces and low-density settlement, which appear similar to a range of other social centres from around the world which also struggle to fit conventional definitions of urbanism. Despite this, discussion of the relevance of such comparison remains limited. Through assessment of the two best investigated oppida in Europe (Bibracte, France and Manching, Germany) we explore the nature of the oppida phenomenon, the commonalities they share, and how these compare with agglomerations elsewhere in the world.